An Efficient Approach for Localization using Trilateration Algorithm based on Received Signal Strength in Wireless Sensor Network - Matharu, Niharika Singh; Buttar, Avtar Singh (International Journal of Computer Sciences and Engineering, 2025)
In this work, an efficient approach without additional hardware and improved accuracy is proposed Trilateration based algorithm is a distributed beacon-based localization algorithm uses distance estimation to compute the 3-D position of nodes in a network with help of Received Signal Strength. The blind node can estimate its distance from anchor node using received signal strength and the position (x, y, z) in 3-D of the node can be computed from the position information obtained from the three and four anchor nodes using trilateration. Signal propagation model is used to find out the received power i.e. received signal strength from different sensor nodes. This method uses this received signal strength. This received signal strength information is used in the trilateration method to find out the exact location of the blind nodes in the sensor field. The average localization error is coming to be 0.0119 computed with 100 anchor nodes.